Dynamics of biochemical and immunological parameters in patients with malignant and benign tumors of the thoracic and lumbar spine - Korzh, Mykola; Radchenko, Volodymyr; Leontyeva, Frieda; Kutsenko, Volodymyr; Shevtsov, Bogdan; Popov, Andrey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
The problem of early diagnosis of neoplasm of the spine remains relevant. One of the most sensitive diagnostic tests for bone tumors is the determination of biochemical and immunochemical markers in the blood serum of patients. Objective: to study biochemical markers and blood serum cytokines that reflect the state of different types of metabolism and the dynamics of the inflammatory reaction in patients with primary tumors of the thoracic and lumbar spine and metastases of extra vertebral tumors to the spine. Methods: blood and immunochemical study of blood serum of 45 patients with primary benign and malignant tumors of the thoracic and lumbar spine of different histological structure, as well as metastases in the vertebral bodies with carcinoma of the extravertebral localization and 11 conditionally healthy middle-aged people. The dynamics of biochemical parameters of carbohydrate, protein and lipid metabolism, as well as serum levels of anti-inflammatory interleukins IL-1β and IL-6, and procalcitonin were evaluated. Results: a significantly higher content of IL-1β, IL-6 and procalcitonin in the blood serum of patients with metastases of different carcinomas in the vertebrae and primary malignant tumors was found in comparison with benign tumors. A significantly higher level of alkaline phosphatase activity was established in patients with primary malignant neoplasms of the thoracic and lumbar spine and metastases in the vertebrae. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> variations in the content of IL-1β, IL-6, and procalcitonin may indicate the stimulation of the inflammatory focus around the tumor and largely reflect their problastic effect. Activation of alkaline phosphatase in patients with primary malignant neoplasms and metastases in the vertebra is probably a confirmation of compensatory activation of osteosynthesis in response to oncogenic osteolysis.